2005
DOI: 10.1163/156856005774382724
|View full text |Cite
|
Sign up to set email alerts
|

The peroxisome proliferator-activated receptor α activator, Wy14,643, is anti-inflammatory in vivo

Abstract: The peroxisome proliferator-activated receptor system is exciting much interest as a novel point of therapeutic intervention in inflammation. Here, the effect of a peroxisome proliferator-activated receptor alpha agonist, [4-chloro-6-(2,3-xylidine)-pyrimidinylthio]acetic acid (Wy14,643), was examined in arachidonic acid-induced murine ear inflammation. 3-[1-(4-Chlorobenzyl)-3-t-butyl-thio-5-isopropylindol-2-yl]-2,2-dimethylpropanoic acid (MK886, a 5-lipoxygenase inhibitor) and indomethacin (a cyclo-oxygenase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Eicosanoids are PPARα activators [36] that can inhibit arachidonic acid-induced inflammation in part by enhancing degradation of leukotriene B4 [37]. It is noteworthy that the expression of ALOX5AP (leukotriene synthesis) and PPARA followed opposite patterns of expression with the AAC treatment indicating that the inflammatory response in those cows likely was of a greater magnitude but of brief duration.…”
Section: Discussionmentioning
confidence: 99%
“…Eicosanoids are PPARα activators [36] that can inhibit arachidonic acid-induced inflammation in part by enhancing degradation of leukotriene B4 [37]. It is noteworthy that the expression of ALOX5AP (leukotriene synthesis) and PPARA followed opposite patterns of expression with the AAC treatment indicating that the inflammatory response in those cows likely was of a greater magnitude but of brief duration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have revealed impaired production of inflammatory cytokines interferon‐γ, IL‐6 and TNF‐α in vitro ( Cunard et al ., 2002 ; Murakami et al ., 2007 ) following exposure to the PPAR‐α ligand WY14643, with similar inhibitory effects on IL‐6 and TNF secretion observed in lipopolysaccharide‐stimulated macrophages following treatment with the PPAR‐α agonist K‐111 (2,2‐dichloro‐12‐(4‐chlorophenyl)dodecanoic acid) ( Murakami et al ., 2007 ). Similarly, the PPAR‐α agonist WY14643 has anti‐inflammatory effects in arachidonic acid‐evoked oedema in the murine ear‐swelling test ( Colville‐Nash et al ., 2005 ). Mice lacking the PPAR‐α receptor have significantly elevated levels of neutrophils, macrophages and TNF‐α following intranasal administration of lipopolysaccharide compared with wild‐type littermates ( Delayre‐Orthez et al ., 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, WY14.643, a potent agonist of PPAR- α , can directly increase the expression of adiponectins, antidiabetics, antiatherosclerosis, and anti-inflammatory effects [143]. …”
Section: Ppar-αmentioning
confidence: 99%